Weed Control in Sweet Corn - William M. Stall (EDIS)
Revised! HS-197, a 5-page fact sheet by William M. Stall, describes effective weed management practices for sweet corn and provides a table of listing herbicides available to growers for chemical weed control. This publication updates the table to reflect current recommendations. Published by the UF Department of Horticultural Sciences, October 2006.